Infra-red thermography to assess water stress and leaf temperature response on páramo rosettes under experimental warming (2017)
"Tropical alpine regions are one of the most important ecosystems in terms of the environmental services they provide, both locally and globally. In Colombia, humid alpine regions are known as páramos and their potential for water purification, storage and regulation makes them strategic ecosystems. Despite of their importance, these ecosystems are being threatened by different human related activities... This study aimed to understand the impact of experimental warming using OTC (open top chambers) in the field on leaf temperature regulation and water stress for three páramo rosettes species: Espeletia argentea, Espeletia grandiflora and Espeletia corymbosa using infra-red thermography. Our results show that leaf temperature of warmed plant increased in E. argentea and E. corymbosa by about 3.5 oC" -- Tomado del Formato de Documento de Grado.